Indocyanine Green Lymphography-guided Ligation to Treat ECMO-related Groin Lymphocele - Albert Lamas Llopis; Sergi Barrantes; Laura Torrano Romero; Silvia de la Torre González; Luís Martínez-Sapiña; JA Palacín Porté; Anna López Ojeda (JPRAS Open)
Extracorporeal Membrane Oxygenation (ECMO) placement in heart transplant patients can lead to the development of a groin lymphocele. Surgery is usually considered when conservative treatment fails. Indocyanine Green (ICG) lymphography enables the identification and ligation of damaged lymphatic vessels responsible for the lymphocele, while preserving intact lymphatic structures. In this paper, we present a case report highlighting the use of ICG lymphography-guided ligation of lymphatic leaks to treat a groin lymphocele following ECMO placement in a heart transplant patient.